2020
DOI: 10.1016/j.ebiom.2020.103044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the pathophysiology of post-sepsis syndrome to identify therapeutic opportunities

Abstract: Sepsis is a major health problem worldwide. As the number of sepsis cases increases, so does the number of sepsis survivors who suffer from “post-sepsis syndrome” after hospital discharge. This syndrome involves deficits in multiple systems, including the immune, cognitive, psychiatric, cardiovascular, and renal systems. Combined, these detrimental consequences lead to rehospitalizations, poorer quality of life, and increased mortality. Understanding the pathophysiology of these issues is crucial to develop ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 120 publications
(206 reference statements)
0
45
0
4
Order By: Relevance
“…The limitation of our study is the unexplored effect of carboplatin in vivo where LPS tolerance is observed such as in sepsis. Sepsis is a systemic inflammatory condition when massive cytokine storms in response to infection is followed by depressed immune response called immune paralysis 39 . Animal models such as two-hit cecal ligation and puncture (CLP), may be used to test whether carboplatin can rescue immune paralysis phenotypes 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of our study is the unexplored effect of carboplatin in vivo where LPS tolerance is observed such as in sepsis. Sepsis is a systemic inflammatory condition when massive cytokine storms in response to infection is followed by depressed immune response called immune paralysis 39 . Animal models such as two-hit cecal ligation and puncture (CLP), may be used to test whether carboplatin can rescue immune paralysis phenotypes 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in high-income countries the long-term survival is improving, with approximately 14 million sepsis survivors each year [ 8 ], raising at the same time new health consequences and a significant burden for patients and society [ 9 , 10 ]. Thus, post-sepsis syndrome involves multiple long-term deficits, including the immune, cognitive, psychiatric, renal, and cardiovascular systems [ 11 , 12 ]. Notably, nearly a quarter of sepsis survivors will be readmitted to hospital within 30 days of discharge [ 13 ].…”
Section: Sepsis As a Global Health Prioritymentioning
confidence: 99%
“…Such effects were correlated with diminishing the systemic IFN-γ synthesis, decrease of microbicidal activities of their neutrophils, phagocytosis and NO production [124]. Cardiac dysfunction is a well-known serious complication of sepsis [125]. A recent study suggested that IL-12p35 [Il12a] may be considered an important target during the management of such complications as its deletion worsened CLP-induced cardiac dysfunction [126].…”
Section: Interleukin-12mentioning
confidence: 99%